2019
DOI: 10.1111/dme.14195
|View full text |Cite
|
Sign up to set email alerts
|

A low‐cost laboratory‐based method for predicting newly diagnosed biopsy‐proven diabetic nephropathy in people with type 2 diabetes

Abstract: Aims To identify significant prognostic factors for newly diagnosed biopsy‐proven diabetic nephropathy using routine laboratory measures, from which to derive a low‐cost explanatory model, and to use this model to examine associations between the potential low‐cost test panels and the risk of diabetic nephropathy in people with type 2 diabetes with normal kidney function. Method A population‐based case–control study was undertaken to test the association between diabetic nephropathy and 47 laboratory variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This observation aligns with numerous findings in the literature, albeit with certain distinctions in specific coagulation parameters. Yu et al [ 7 ] discerned elevated levels of FIB, FDP, D-D, APTT, and TT in diabetic nephropathy (DN) patients compared to those with uncomplicated diabetes. However, their study did not clarify if these differences remained statistically significant after accounting for confounding variables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation aligns with numerous findings in the literature, albeit with certain distinctions in specific coagulation parameters. Yu et al [ 7 ] discerned elevated levels of FIB, FDP, D-D, APTT, and TT in diabetic nephropathy (DN) patients compared to those with uncomplicated diabetes. However, their study did not clarify if these differences remained statistically significant after accounting for confounding variables.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, DKD is recognized as a chronic microvascular complication of diabetes mellitus, and a growing body of evidence underscores its intimate association with coagulation anomalies. Some studies have shown a significant association of coagulation parameters with the onset and progression of DKD, whereas others failed to replicate this association [7][8][9][10]. For instance, a cross-sectional investigation from central China indicated that coagulation markers such as FIB, FDP, D-D, APTT, and TT were notably elevated in DKD patients compared to those devoid of diabetic complications [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation